Best Answer

X2+11x+11 = 7x+9

X2+11x-7x+11-9 = 0

x2+4x+2 = 0

Solve as a quadratic equation by using the quadratic equation formula or by completing the square:

x = -2 + or - the square root of 2

Q: X2 plus 11x plus 11 equals 7x plus 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

11x - 21 = 7x + 3 4x = 24x = 6

11x + 2 = 26 + 7x Subtract 7x from both sides: 4x + 2 = 26 Subtract 2 from both sides: 4x = 24 Divide both sides by 4: x = 6

4y + 3w + 4x + 9y + 7x - 7w (combine like terms)-4w + 11x + 13y

7x+y=6

-7x - 2y = -3

Related questions

x2+11x+11 = 7x+9 x2+11x-7x+11-9 = 0 x2+4x+2 = 0 The above quadratic equation can be solved by using the quadratic equation formula and it will have two solutions.

7x + 8 = 11x + 3, solve for xsubtract 7x from both sides8 = 11x - 7x + 38 = 5x + 3subtract 3 from both sides5 = 5xdivide both sides by 51 = x.

11x - 21 = 7x + 3 4x = 24x = 6

x=4 x=0

x=3

If: 11x+25 = 7x+15 then there is only one solution and it is x = -2.5

11x+9=7x+21 11x-7x=4 4x+9=21 21-9=12 4x=12 12 divided by 4= 3 x=3

It is a linear equation in a single variable, x.

x=3 actually its 7

11x + 2 = 26 + 7x Subtract 7x from both sides: 4x + 2 = 26 Subtract 2 from both sides: 4x = 24 Divide both sides by 4: x = 6

4x + 8 + 7x + 12 = 11x + 20

4x + 6 = -82 - 7X add 7X to each side 4X + 7X + 6 = -82 -7X + 7X 11X + 6 = -82 subtract 6 from each side 11X + 6 - 6 = -82 - 6 11X = -88 divide both sides by 11 X = -8 check in original equation 4(-8) + 6 = -82 - 7(-8) -32 + 6 = -82 + 56 -26 = -26 checks